Pengaruh Teknologi Informasi dan Modal Kerja terhadap Daya Saing UMKM di Kota Bengkulu - Yudi Irawan Abi; Tri Febrina Melinda; Desti Rupita Sari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to examine the role of information technology and working capital with the competitiveness of UMKM in Bengkulu City. This study uses a quantitative methodology to solve the problem. The sampling technique in this study used a purposive sampling technique and data collection was carried out by distributing questionnaires to respondents. Data collection techniques using a questionnaire that has been tested for validity and reliability. The number of samples is 50 UMKM in the city of Bengkulu. The data analysis technique used in this research is multiple regression analysis using SPSS 21. Hypothesis testing using t test. The results of this study indicate that information technology has a significant positive effect on competitiveness and working capital has a significant effect on competitiveness of UMKM in Bengkulu city.